Pengaruh Suhu Pengeringan Daun Kenikir (Cosmos caudatus K.) terhadap Sifat Kimia dan Organoleptik Teh Herbal Celup - Widhi Aiman Zakiy; R. Hermawan; Nur Rohmah Lufti A’yuni (Journal of Food Security and Agroindustry, 2026)
This study aimed to evaluate the effect of drying temperature on the chemical and organoleptic properties of formulated kenikir (Cosmos caudatus K.) herbal tea bags. The experiment was arranged using a Completely Randomized Design (CRD) with a single factor, namely drying temperature at 40, 50, 60, 70, and 80°C with three replications, resulting in 15 experimental units. Kenikir leaves were dried prior to formulation with green tea (50%), kenikir leaves (30%), and jasmine (20%). Treatments at 40°C and 50°C were not further analyzed due to moisture content exceeding the standard limit (>8%). The analyses included moisture content, yield, total phenolic content (Folin–Ciocalteu method), total flavonoid content (AlCl₃ method), antioxidant activity (DPPH method), and sensory evaluation (color, aroma, and taste). Data were analyzed using analysis of variance (ANOVA) at a 5% significance level followed by Duncan’s Multiple Range Test (DMRT). The results showed that increasing drying temperature significantly decreased moisture content and yield (p<0.05), while increasing total phenolic and flavonoid contents. The highest antioxidant activity was observed at 60°C with an inhibition value of 33.68%, although it was not significantly different among treatments (p>0.05). Meanwhile, the highest phenolic and flavonoid contents were obtained at 80°C. Sensory evaluation indicated that the 80°C treatment had the highest level of panelist preference. In conclusion, drying temperature significantly affects the chemical and sensory characteristics of formulated herbal tea, with 60–80°C considered the optimal range depending on the evaluated parameters.